Estendendo o Modelo de Organização de Sistemas Multiagentes PopOrg com Unidades Organizacionais Recursivas - Rosa, Simone Escouto da; Dimuro, Graçaliz Pereira; Costa, Antônio Carlos da Rocha (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2010)
This work presents a proposal of a recursive approach for the definition of the concept of organizational unities (or, more generally, social systems) in the macrolevel structure of the multiagent system organizational model called PopOrg (Population-Organization Model). The implementation relations of the micro-and macrolevel structures of the PopOrg Model will be also studied recursively in this approach. A visual language, based on diagrams, will be developed to allow the graphical representation of the elements of the model, like the population, the micro-and macro-level structures, the implementation relations, and also the relationships between the organization unities in the macro-level structure.